Study on knowledge and perceptions on the uptake of non-medicinal cannabis-substances and preparations by Portuguese consumers: Borderline issues - Alexandre Elias; Catarina Rosado; Maria do Céu Costa (Heliyon)
Cannabis sativa L.-based food supplement products in pharmacies and para pharmacies in Portugal increased by 84 % between 2021 and 2022, arousing consumers' curiosity. However, information about these products is limited, and consumers are not aware of the restrictions in current European regulations. This study aims to understand Portuguese consumers' perceptions of cannabis products and identify the distribution channels and market strategy. A cross-sectional investigation on the consumption of non-medicinal products derived from cannabis occurred using a survey that aimed to collect data covering four main research questions: consumer information, consumed products, level of satisfaction, and used channels for purchasing products. Applying an original questionnaire aimed at the public via email and social networks, 176 responses were collected, where a high degree of satisfaction with taking cannabis-based products was evident, with sleep disorders and the promotion of well-being as the reasons (48,5 %) that led to the majority of respondents to seek out these products. Health professionals are already recommending cannabis-derived products; however, most respondents are unable to differentiate a food supplement from a medicine. Online purchase was the respondents' favourite choice, and respondents (93 %) were unaware of the properties of food supplements in general. Consumers ignore that the parts of the cannabis plant, whose active ingredients they expect to have a greater capacity to promote well-being, namely cannabinoids, are not authorized by the European Food Safety Authority (EFSA) to be marketed in foods or dietary supplements.Results also show that the influence of media in Portugal is significant in the choice of products, together with the lack of information on cannabis-based supplements and medicines, highlighting the need for a pro-consumer review, and promoting conscious and informed choices. Thus, we propose creating a Community Knowledge on Food Supplements linking academics, stakeholders, and authorities.